Assessing ESP in ’Math Technique’ Branches The Case of Civil Engineering BAC English Tests from 2010 to 2015 - NAOUA, Mohammed (Journal of Human Sciences, 2017)
In ESP testing, we are concerned with making inferences about the extent to which test takers can use language in contexts similar to their fields of study. In order to justify the score interpretations, and the purposes for which theyare intended to be used, two types of authenticity need to be provided. First, the pupils’ instructional syllabus needs to correspond to language situations in specific target domains.Second, tests should sample their content and tasks from ESP relevant contexts. In this article, we attempt to conduct an empirical analysis to examine the extent to which these criteria are implementedin civil engineering specialties at the secondary school.